2019
DOI: 10.1186/s40659-019-0227-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and subcellular localization of six HDACs and their roles in response to salt and drought stress in kenaf (Hibiscus cannabinus L.)

Abstract: Background Histone acetylation is an important epigenetic modification that regulates gene activity in response to stress. Histone acetylation levels are reversibly regulated by histone acetyltransferases ( HATs ) and histone deacetylases ( HDACs ). The imperative roles of HDACs in gene transcription, transcriptional regulation, growth and responses to stressful environment have been widely investigated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 52 publications
(47 reference statements)
1
14
0
Order By: Relevance
“…This process is catalyzed by histone acetyltransferases (HaTs) and histone deacetyltransferases (Hdacs), which are responsible for adding and removing acetyl groups from histone tails, respectively. Hdac-mediated acetylation is associated with ischemic heart disease (11). application of trichostatin a (TSa), a class i and class ii Hdac inhibitor alters the response to myocardial ischemic injury in the heart and limited areas of Mi (12).…”
Section: Introductionmentioning
confidence: 99%
“…This process is catalyzed by histone acetyltransferases (HaTs) and histone deacetyltransferases (Hdacs), which are responsible for adding and removing acetyl groups from histone tails, respectively. Hdac-mediated acetylation is associated with ischemic heart disease (11). application of trichostatin a (TSa), a class i and class ii Hdac inhibitor alters the response to myocardial ischemic injury in the heart and limited areas of Mi (12).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, high acetylation levels of H3K and low acetylation levels of H3K27 and H4K5 were observed following a lower PEG treatment. Meanwhile, acetylation levels of H3K9, H3K27 and H4K5 were all reduced in response to a higher PEG treatment [74].…”
Section: Hdacsmentioning
confidence: 95%
“…For example, DoHDA10 and DoHDT4 were highly up-regulated after PEG-mediated drought treatment, while other HDAC genes were not changed [52]. Wei et al studied the roles of six HDACs in response to drought stress in kenaf and found up-regulation of all these HDACs after PEG treatments [74]. In addition, high acetylation levels of H3K and low acetylation levels of H3K27 and H4K5 were observed following a lower PEG treatment.…”
Section: Hdacsmentioning
confidence: 99%
“…The Arabidopsis class I (HDA19) and class II (HDA5/14/15/18) REDUCED POTASSIUM DEPENDENCY3 (RPD3)-like family histone deacetylases control positive and negative salinity stress responses, respectively, by acting conversely in the expressions of salt-responsive genes, such as ABI5 , NCED4 , GA20x7 , LEA4 _ 2 , P5CS1 , and NAC016 / 019 [ 69 , 70 ]. In addition, the enhanced gene expression of six histone deacetylases HcHDA2, HcHDA6, HcHDA8, HcHDA9, HcHDA19, and HcSRT2 in kenaf ( Hibiscus cannabinus ) during salinity stress is associated with the levels of H3K9ac, H3K27ac, and H4K5ac, but has not yet been linked to other stress-induced transcriptional responses [ 100 ]. The Arabidopsis floral initiator Shk1 kinase binding protein1 (SKB1), a type II arginine methyltransferase, regulates transcription and pre-mRNA splicing of FLOWERING LOCUS C ( FLC ) and the stress-responsive genes, such as HAB1 , MEK1 , MEKK1 , and MRK1 , during salinity stress by dissociating from chromatin and altering the methylation status of histone 4 arginine 3 (H4R3) symmetric demethylation (H4R3sme2) and small nuclear ribonucleoprotein Sm-like4 (LSM4) [ 71 ].…”
Section: Chromatin Dynamics Associated With Abiotic Stress-inducedmentioning
confidence: 99%